PENGEMBANGAN ALUMNI RELATION MANAGEMENT FTI UKDW BERBASIS WEBSITE SEBAGAI MEDIA MEMPERERAT RELASI DENGAN ALUMNI - Ivan Pradipta Gunawan; Restyandito Restyandito; Rosa Delima (Jurnal Sistem Informasi dan Informatika (Simika), 2025)
Universities face the challenge of a lack of alumni engagement, with many losing contact after graduation. This results in difficulties in leveraging alumni potential. Insufficient communication leads alumni to feel that their relationship with the university is limited to their time as students. The low response rate to Tracer Studies, which track alumni careers and gather feedback, highlights this issue. Data from various universities indicate low response rates, primarily due to weak relationships and alumni's lack of awareness about the importance of Tracer Studies. Therefore, the development of an Alumni Relation Management system is necessary. The development of a web-based Alumni Relation system used the prototyping method. Evaluation was conducted using Heuristic Evaluation with experts, followed by system implementation through email campaigns to enhance alumni-university engagement. These steps aim to address alumni engagement issues and improve Tracer Study response rates. System testing was performed using black box testing and usability testing. The results indicated that the system functions well in both functional and non-functional aspects. Based on these findings, the system is ready for use and is expected to enhance alumni engagement and the effectiveness of Tracer Studies.